IMPLEMENTASI TIPE KEPEMIMPINAN PARTISIPATIF KEPALA UPT SMKN 9 WAJO - A.Syarmadana; Isnidiyahningsih; Fadillah Reski Amaliah; Ismail Bakri; Syamsiar; Besse Herlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyze the implementation of participative leadership by the Head of UPT SMKN 9 Wajo. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The results show that the principal implements participative leadership by actively involving teachers and staff in decision-making, maintaining open communication, and providing trust through task delegation. This implementation has a positive impact on performance, work motivation, and a collaborative work atmosphere. The study suggests the need to strengthen a participative culture within the school environment to improve the effectiveness of educational management.